Siamese: scalable and incremental code clone search via multiple code representations - Chaiyong Ragkhitwetsagul (2020)
© 2019, Springer Science+Business Media, LLC, part of Springer Nature. This paper presents a novel code clone search technique that is accurate, incremental, and scalable to hundreds of million lines of code. Our technique incorporates multiple code representations (i.e., a technique to transform code into various representations to capture different types of clones), query reduction (i.e., a technique to select clone search keywords based on their uniqueness), and a customised ranking function (i.e., a technique to allow a specific clone type to be ranked on top of the search results) to improve clone search performance. We implemented the technique in a clone search tool, called Siamese, and evaluated its search accuracy and scalability on three established clone data sets. Siamese offers the highest mean average precision of 95% and 99% on two clone benchmarks compared to seven state-of-the-art clone detection tools, and reported the largest number of Type-3 clones compared to three other code search engines. Siamese is scalable and can return cloned code snippets within 8 seconds for a code corpus of 365 million lines of code. Using an index of 130,719 GitHub projects, we demonstrate that Siamese’s incremental indexing capability dramatically decreases the index preparation time for large-scale data sets with multiple releases of software projects. The paper discusses the applications of Siamese to facilitate software development and research with two use cases including online code clone detection and clone search with automated license analysis.